Focusing on antimicrobial resistant infections –are we missing the forest for the trees and the patients for pathogens? - Lawandi, Alexander; Kadri, Sameer S.; Powers, John H. (Frontiers in Antibiotics, 2023)
Antimicrobial resistance (AMR) is a challenge because it is associated with worse patient outcomes. To solve the problem will take development of interventions and policies which improve patient outcomes by prolonging survival, improving patient symptoms, function and quality of life. Logically, we should look to focusing resources in areas that would have the greatest impact on public health. AMR takes the approach of focusing on individual pathogens and “pathogen-focused” development. However, evaluating overall infections and their impact on patient outcomes reveals that 17 of 18 infection deaths are associated with susceptible pathogens. Here we discuss recentering on patients and patient outcomes instead of pathogens, and propose six suggestions on how a patient focus impacts areas and incentives for clinical research.